Efektivitas Fungsi Pengawasan Komisi Pengawas Persaingan Usaha (KPPU) Kanwil VI Makassar Dalam Mencegah Praktek Monopoli Perdagangan Perspektif Hukum Islam - Noranisa; Fathurahman; Paikah, Nur (Journal of Islamic Economic Studies, 2025)
This study aims to describe the implementation of the supervisory function of the Indonesia Competition Commission (KPPU) Regional Office VI in Makassar City in preventing monopolistic trade practices, as well as to review it from the perspective of Islamic Law. This research is classified as field research, with primary data obtained through direct interviews with KPPU Regional Office VI employees, and secondary data sourced from books, official documents, and research reports. The results of the study indicate that KPPU conducts supervision through information gathering, receiving public complaints, and conducting on-site inspections. If violations are found, further investigations are carried out to collect evidence. The challenges faced include legal limitations, inadequate facilities and infrastructure, low public awareness, and limited human resources, all of which hinder the effectiveness of KPPU's supervisory implementation. From the perspective of Islamic Law, the supervision conducted by KPPU aligns with the principle of Al-Muraqabah and can be analogized to the Al-Hisbah institution during the time of the Prophet Muhammad (SAW) and the Khulafā’ al-Rāshidīn, which was responsible for monitoring markets based on the values of honesty, justice, trustworthiness, and mutual cooperation. KPPU, as an institution established under statutory mandate, represents the authority of Ulil Amri* within the Islamic constitutional framework. The implication of this research is the need to strengthen cooperation between the government, KPPU, and society to prevent monopolistic trade practices, as well as to enhance KPPU's authority in investigations in order to realize a just economic democracy.